Economics myths in the great population debate - TAN, Kim Song (Institutional Knowledge at Singapore Management University, 2014)
3 ECONOMIC ECONOMIC MYTHS IN THE MYTHS IN THE GREAT GREAT POPULATION POPULATION DEBATE DEBATE Donald Low, Yeoh Lam Keong, Tan Kim Song, and Manu Bhaskaran Practical men, who believe themselves to be quite exempt from any intellectual influences, are usually the slaves of some defunct economist. —John Maynard Keynes The debate on the Population White Paper has surfaced a number of myths and fallacies that seems to dominate the current discussion on Singapore’s population policies. Economics provides us with a very useful set of analytical tools to clarify thinking and to develop sensible, evidence-based policies. The purpose of this essay is to examine some of the ways these myths have inadvertently, or even subconsciously, been used to justify inaccurate thinking about policies.1 Myth #1: GDP growth, no matter how it is achieved, is an unambiguously good thing There seems to be an implicit and unspoken assumption that Singapore must continue to grow at a certain rate, and that if the growth does not come from labour productivity increases, then it must come from labour force increases. This is poor economic reasoning. GDP growth per se does not improve individual well-being; it only does if it is driven by productivity improvements that raise workers’ wages. If labour productivity is not increasing, it means that whatever GDP growth we “achieve” comes from brute force (i.e., injection of more labour inputs). Not only does this not increase society’s well-being, it actually reduces it. If the 3 per cent GDP growth that the government aims for is attained by a 3 per cent labour force increase, Singaporeans are no better off in per capita terms. Meanwhile, they have to contend with negative externalities such as more congestion and competition for public goods, depressed wages, inflation and higher asset prices, and dilution of national identity. Associated with the growth fetish is a somewhat irrational fear of zero GDP growth. There seems to be an implied belief that high GDP growth driven mainly by labour force injections is superior to slow or zero GDP growth. This is again bad economics. Consider a country whose GDP has stagnated. Its labour force is declining (say because of an ageing population), but it manages to eke out productivity improvements of 1–2 per cent annually. In gross terms, the country is not producing more. But per capita GDP is increasing, and incomes and standards of living are still rising because of productivity growth. This scenario describes Japan’s current situation. Obviously , this is an extreme scenario; no one is recommending zero GDP growth for Singapore. But even in this extreme scenario, it is clear that zero GDP growth does not spell the end of rising incomes and standards of living. Historically much slower growth rates (of, say, 2 per cent) should not be feared as long as all (or most) of that growth comes from increases in labour productivity. HARD CHOICES 41 Myth #2: If we don’t have sufficiently large injections of foreign labour, business costs will rise, some businesses will shut down or move out of Singapore, and Singaporean workers will be laid off Businesses that rely on cheap foreign labour receive an implicit subsidy from the rest of society. The low cost of labour encourages them to persist with low value-added production and discourages them from upgrading and improving their business processes. Meanwhile , cheap foreign labour discourages automation and holds down wages for citizen workers doing the same job. If the Singapore government were to tighten foreign worker policies over a sustained period, there is no doubt some businesses would not be able to adapt and would have to move out of Singapore or shut down. Is this necessarily a bad thing? No, in a vibrant capitalist economy, this is exactly what one expects. Businesses that cannot adapt should and will exit the market; the state should not be propping them up with ever more inputs of cheap labour. Their exit also frees up labour and capital resources for the more productive parts of the economy. Such “creative destruction” is a necessary part of the economic restructuring process. In economic restructuring, there will always be some firms that are disadvantaged. The economically sensible decision is not to protect these firms in their existing labour-intensive state (which imposes high social costs) through easy access to cheap foreign labour. Instead, the government can help lessen the pain in this process. For instance, it can help local SMEs...